Mild hypothermia and hemorrhagic lesions in neonates with hypoxic-ischemic encephalopathy: experience in an outborn center. (17th June 2016) - Savarese, Immacolata; Balestri, Martina; Piersigilli, Fiammetta; Giliberti, Paola; Campi, Francesca; Rechichi, Jole; Mondì, Vito; Gesualdo, Francesco; Longo, Daniela; Cilio, Maria Roberta; Dotta, Andrea
Abstract: Objective : Therapeutic hypothermia (TH) started within six hours from birth has been shown to improve neurodevelopmental outcomes in newborns with moderate-to-severe hypoxic-ischemic encephalopathy. Methods : Twenty-nine consecutive newborns treated with whole body cooling at the Bambino Gesú Children's Hospital between March 2011 and December 2012 were included in this study. All infants were out-born neonates. Passive cooling was always started at the birth center and continued during transportation. Pre- and post-transport risk index of physiological stability (TRIPS) scores were calculated for each patient to evaluate the impact of the transportation. Magnetic resonance imaging (MRI) was performed within 10 days of life to investigate the presence of brain injury. Results : Among the 26 survivors, 14 had no detectable lesions and 12 presented with brain injury on MRI. Four babies presented with cerebral bleeding. Babies with cerebral hemorrhage had a worse pre-transport TRIPS score, but among these neonates no worsening between pre and post-transport score was registered. Conclusion : The presence of cerebral hemorrhagic lesions seemed to be related to the initial clinical conditions of the baby rather than to the transport itself. Our data confirm that TH performed in an out-born center is efficient and safe.